Fish Traps in Inland Waters of North Kerala - M.P., Remesan; A., Ramachandran (Fishery Technology, 2025)
Result of the study on traditional traps in the inland waters of three northern districts viz. Kasargod, Kannur and Kozhikode in Kerala state during 2003-2004 is presented. Mainly six types of traps are found in operation. Chempally koode is a rectangular bamboo trap with "D" shape in cross section operated without bait in some rivers of Kannur and Kasargod. Bamboo screen barriers are almost completely replaced with durable HDPE net screen to make handling easy. Thottil vala is a unique aerial trap operated from the dam in Pazhassi reservoir during monsoon to catch big fishes jumping against flowing water. Therakkal using filter trap is a primitive fishing method seen in the backwaters of Kuppam river. Due to the scarcity of resources and proliferation of other gears operation of fish traps has declined. The design, fabrication, mode of operation and economics of important traps used in the region are discussed along with conservation aspects.